Reducing the gender asset gap through agricultural development: A technical resource guide - Quisumbing, Agnes R.; Meinzen-Dick, Ruth S.; Johnson, Nancy L.; Njuki, Jemimah; Behrman, Julia A.; Gilligan, Daniel O.; Kovarik, Chiara; Peterman, Amber; Roy, Shalini; Waithanji, Elizabeth; Rubin, Deborah; Manfre, Cristina (International Food Policy Research Institute, 2014)
This guide explores the intersection of gender and assets in the context of agricultural interventions. It grows out of a collaborative effort among international agricultural research organizations, implementing partners, and monitoring and evaluation (M&E) partners who came together to evaluate the impact of agricultural interventions on the ability of men and women to use, control, and own key productive assets. The project was implemented by researchers at the International Food Policy Research Institute (IFPRI) and the International Livestock Research Institute (ILRI) under the Gender, Agriculture, and Assets Project (GAAP) with primary support from the Bill & Melinda Gates Foundation (BMGF).